Scott Slovic, Swarnalatha Rangarajan, and Vidya Sarveswaran (Eds). (2022). The Bloomsbury Handbook to Medical-Environmental Humanities - Rosenthal, Debby (Journal of Ecohumanism, 2023)
Scott Slovic, Swarnalatha Rangarajan, and Vidya Sarveswran (Eds). (2002). The Bloomsbury Handbook to Medical-Environmental Humanities. Bloomsbury Academic Press. ISBN: 978-1-3501-9730-5